2017
DOI: 10.1016/j.ejca.2017.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Current margin practice and effect on re-excision rates following the publication of the SSO-ASTRO consensus and ABS consensus guidelines: a national prospective study of 2858 women undergoing breast-conserving therapy in the UK and Ireland

Abstract: There continues to be large variation in margin policy and re-excision rates across units. Altering margin policies to follow either SSO-ASTRO or ABS guidelines would result in a modest reduction in the national re-excision rate. Most re-excisions are for involved margins rather than close margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…Re-excision is required when histopathology-based post-operative tests indicate that either the tumour is too close to the specimen margins or the tumour infiltrates the margins. Re-excision rates vary from centre to centre; a recent prospective study indicated a 0% to 41% (median 17.2%) re-excision rate across 76 individual centres in the UK (Tang et al 2017 ). Re-operation can cause patients additional stress and affect cosmetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Re-excision is required when histopathology-based post-operative tests indicate that either the tumour is too close to the specimen margins or the tumour infiltrates the margins. Re-excision rates vary from centre to centre; a recent prospective study indicated a 0% to 41% (median 17.2%) re-excision rate across 76 individual centres in the UK (Tang et al 2017 ). Re-operation can cause patients additional stress and affect cosmetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, up to 20% of patients may require additional surgery for re-excision of margins involved with tumour following histopathological assessment [10]. This has considerable impact on patient well-being and significant resource implications for the NHS [11] and although many international centres now accept the pathological definition of a clear margin as 'no tumour at the inked resection margin' [12], current practice continues to vary across the UK [13].…”
Section: Problems With Current Management Strategiesmentioning
confidence: 99%
“…Definitive BCS is associated with similar survival rates to those achieved with mastectomy. Unfortunately, on average, 18 per cent of patients with ductal carcinoma in situ (DCIS) and 27 per cent of those with invasive disease undergoing BCS in the UK require reoperation for positive margins. Positive margins after BCS are associated with a twofold increased risk of ipsilateral breast tumour recurrence, which is not negated by radiotherapy, systemic therapy or endocrine therapy.…”
Section: Introductionmentioning
confidence: 99%